2021
DOI: 10.3389/fdmed.2021.687638
|View full text |Cite
|
Sign up to set email alerts
|

Saliva as a Source of Biomarkers for Periodontitis and Periimplantitis

Abstract: Saliva has the potential to be used as a diagnostic and monitoring tool for various diseases if biomarkers of an adequate sensitivity and specificity could be identified. Several reviews and even meta-analyses have been performed in recent years, which have found some candidate biomarkers for periodontitis, like macrophage inflammatory protein-1 alpha, interleukin-1ß, interleukin-6, matrix metalloproteinase-8, or hemoglobin. However, none of those are currently in use to replace conventional periodontal diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 89 publications
1
16
0
Order By: Relevance
“…We observed a positive correlation between periodontal markers (MGI, PPD, and CAL) and salivary arginase in groups II and III on day 0 and day 90 ( Table 3 and Table 4 ). Similar results were obtained by Haririan et al who found an improvement in clinical parameters with a reduction in salivary arginase levels following non-surgical periodontal treatment [ 26 ]. The subsequent reduction in levels of salivary arginase indicates that arginase levels are directly related to periodontal health status.…”
Section: Discussionsupporting
confidence: 88%
“…We observed a positive correlation between periodontal markers (MGI, PPD, and CAL) and salivary arginase in groups II and III on day 0 and day 90 ( Table 3 and Table 4 ). Similar results were obtained by Haririan et al who found an improvement in clinical parameters with a reduction in salivary arginase levels following non-surgical periodontal treatment [ 26 ]. The subsequent reduction in levels of salivary arginase indicates that arginase levels are directly related to periodontal health status.…”
Section: Discussionsupporting
confidence: 88%
“…Since the late 1980s, interest in using biomarkers to diagnose and monitor periodontal disease has shown a remarkable increase 28 . Researches in this field have reached a milestone with recognition of several biomarkers with high diagnostic accuracies such as aMMP‐8 which is currently available as a commercial point‐of‐care product.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, saliva has become the focus as a noninvasive diagnostic fluid for oral and systemic diseases, due to its great accessibility and its non-invasive, easy and low-cost collection [19]. Many inflammatory mediators associated with peri-implant mucositis and periimplantitis, such as IL-6, IL-8, MMP-8 (matrix metalloproteinase 8), IL-1β and TNF-α, have been identified as potential biomarkers [35].…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies investigating the salivary concentration of cytokines in the cases of periimplantitis [5,18,19]. However, studies predicting disease, mainly marginal bone loss (MBL), an essential component of prevention, are scarce.…”
Section: Introductionmentioning
confidence: 99%